2017
DOI: 10.3390/genes8080200
|View full text |Cite
|
Sign up to set email alerts
|

Large Introns of 5 to 10 Kilo Base Pairs Can Be Spliced out in Arabidopsis

Abstract: Most of the eukaryotic genes contain introns, which are removed from the pre-RNA during RNA processing. In contrast to the introns in animals, which are usually several kilo base pairs (kb), those in plants generally are very small, which are mostly from dozens of base pairs (bp) to a few hundred bp. According to annotation version 10.0 of the genome of Arabidopsis thaliana, there are 127,854 introns in the nuclear genes; 99.23% of them are less than 1 kb, and only 16 introns are annotated to be larger than 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Trimmed files were then mapped to the genome by STAR using --outFilterMultimapNmax 1 --alignIntronMax 10000 --alignMatesGapMax 10000 --outFilterScoreMinOverLread 0.9 options. Intron length limit (10,000 bp) were set based on the characteristics of the Arabidopsis genome (Chang et al, 2017). Please consult Supplemental Table 2 for basic statistics applied on RNA-seq datasets.…”
Section: Bioinformatic Analysesmentioning
confidence: 99%
“…Trimmed files were then mapped to the genome by STAR using --outFilterMultimapNmax 1 --alignIntronMax 10000 --alignMatesGapMax 10000 --outFilterScoreMinOverLread 0.9 options. Intron length limit (10,000 bp) were set based on the characteristics of the Arabidopsis genome (Chang et al, 2017). Please consult Supplemental Table 2 for basic statistics applied on RNA-seq datasets.…”
Section: Bioinformatic Analysesmentioning
confidence: 99%
“…According to data shown in the TAIR 10.0 annotation of the Arabidopsis genome and our previous analysis ( Chang et al. 2017 ), the Arabidopsis genome has 62,565 introns that are shorter than 100 bp, and these constitute 48.93% of all the introns in the genome.…”
Section: Resultsmentioning
confidence: 91%
“…During evolution, introns show signs of extension and retraction. We have shown that transposable elements and large indels could be the causes of this phenomenon for large introns in Arabidopsis ( Chang et al. 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have found such large introns in other genes involved in meiosis such as FIGL1 , HEI10 , KU70 , Met1A , and MSH2 but their significance remains to be determined. It is possible that they could relate to gene expression regulation as reported in Drosophila where large introns can promote alternative splicing ( Kandul and Noor, 2009 ) although only 16 such large introns (>5kbp) were found in Arabidopsis ( Chang et al, 2017 ). Although we detected eight RTEL1 transcripts in barley anther and meiocyte transcriptome ( Barakate et al, 2021 ), only one isoform was expressed.…”
Section: Discussionmentioning
confidence: 99%